Home, House and Violence: A "Ghastly Domestic Tragedy," Invercargill, 1908 - Wood, Peter (Architectural History Aotearoa, 2025)
For New Zealanders, the first decade of the twentieth century was a reckoning with late nineteenth century national mythologies of a "farmer backbone" society where social health was promised by an abundant agricultural economy (Belich Paradise Reforged p 153). But despite claims that a shift to cities would produce an inferior breed of New Zealander, in 1911 we official became an urban society (of which Ben Schrader drolly observed that fears of catastrophic national decline failed to materialise (Schrader "City Images" np.)). The corollary of urbanisation was the consolidation, through the 1900s, of the New Zealand suburb. Colloquially, this eventually becomes the cultural foundation of the "dream" of Pākehā culture, where Kiwis live in their own homes, insulated from the world in what would become a folk tale paradise of quarter acres, half-gallons, and Pavlova pie (Mitchell The Half-gallon Quarter-acre Pavlova Paradise). But in Invercargill, in 1908, the fallacy of suburban paradise was confronted even as it was being forged. In the early hours of April 8th, in an action of inexplicable and horrifying violence, James Reid Baxter killed his wife, his five children, and then himself in an act of familicide ("Tragedy in Invercargill" p 9). This heartbreak has been largely forgotten, and the human cost of the Invercargill Tragedy might have been best kept respectfully distanced from academic research were it not for the unusually explicit domestic descriptions of the suburban crime scene that were published at the time. Preceding the mores of modern journalism, and taking place prior to the widespread availability of photographic reproduction in newspapers, these accounts provide a unique, if uncomfortable account of domesticity at this time. This features full descriptions of the domestic interior, but, in a context where the perpetrator’s motives remained elusive, the accounts go further and offer insight into the social norms and patterns of the 1900s home. In this paper I unpick the architectural story of the domestic functioning of the Baxter family, as described at the time. In this procedure I am not seeking to sensationalise the violence, nor "solve" the crime. What I will do is explore the representational narratives of 1900s domesticity this case provides. In my argument the vivid descriptions of the Invercargill Tragedy spoke to a genuine desire at the time to understand the unthinkable, and it may be that the reason such domestic violence slipped so quickly from public consciousness was a realisation that actions cannot be simply blamed on houses, however suburban.